Penertiban Izin Usaha Mebel di Kecamatan Alak Kelurahan Manutapen Kota Kupang (Kajian Yuridis Terhadap Peraturan Daerah dan Peraturan Pemerintah) (Deposisi: Jurnal Publikasi Ilmu Hukum, 2025)
This study aims to analyze and describe the regulation of furniture business permits in Alak District, Manutapen Village, Kupang City, within the framework of regional and national legal provisions. Business permits are a vital aspect of legality, providing legal certainty and protection for entrepreneurs. Despite this importance, many wooden furniture businesses continue to operate without official permits. Several factors contribute to this issue, including limited knowledge of regulatory requirements, inadequate access to facilities and administrative services, and the perception among entrepreneurs that small-scale businesses do not necessarily require permits. This research adopts an empirical approach, employing semi-structured interviews with local furniture business owners who have not yet obtained permits. The findings reveal that although the government has made efforts to disseminate information and promote the importance of business permits, these initiatives have not been fully effective. Many entrepreneurs remain unaware of the legal obligations and the potential benefits that permits can provide, such as protection against legal disputes and opportunities for broader business development. The study further identifies both positive and negative impacts of the furniture industry in the local community. On the positive side, furniture businesses significantly contribute to household income, create new job opportunities, and foster creativity through innovative craftsmanship. On the negative side, they also cause environmental issues such as waste and pollution, reduce agricultural land due to the expansion of workshops, and influence lifestyle changes within the community. Based on these findings, the study concludes that the government must strengthen its role by enhancing outreach and education programs, simplifying the permit application process, and providing better support services to entrepreneurs. Additionally, active participation from business owners is crucial to ensure compliance with legal frameworks and to achieve a sustainable balance between economic growth, social welfare, and environmental preservation.